2017
DOI: 10.1111/hdi.12526
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of children and families treated with hemodialysis

Abstract: The assessment of QoL in pediatric patients would allow for the earliest possible identification of their nonsomatic problems and irregularities. This could, consequently, contribute to improving QoL in both children with chronic kidney disease and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
1
14
1
4
Order By: Relevance
“…Two studies [25, 28] assessed QoL in patients undergoing dialysis (haemodialysis /PD) and renal transplantation, whereas another [9] assessed QoL in children undergoing dialysis (haemodialysis /PD) and conservative treatment. One paper measured QoL in a homogeneous population: haemodialysis in children aged 2 to 18 years [27]. The results of this study are along the same lines as ours, but the analysis does not address the same age group, and comparisons with healthy children are not sex- and age-matched.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Two studies [25, 28] assessed QoL in patients undergoing dialysis (haemodialysis /PD) and renal transplantation, whereas another [9] assessed QoL in children undergoing dialysis (haemodialysis /PD) and conservative treatment. One paper measured QoL in a homogeneous population: haemodialysis in children aged 2 to 18 years [27]. The results of this study are along the same lines as ours, but the analysis does not address the same age group, and comparisons with healthy children are not sex- and age-matched.…”
Section: Discussionmentioning
confidence: 91%
“…It can be attributed to a relatively small sample and thus a lack of statistical power. Previous studies have reported that the school functioning among dialysis children was significantly lower than in healthy children [11, 27, 28]. Transportation and many hours in hospitals make it difficult or even impossible to integrate with school peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood chronic diseases usually affect family functioning. Chronic disease greatly increases children's dependency on parents/caregivers (usually mothers) as they face new problems associated with caring for a child with chronic disease [1]. Furthermore, family plays an important role in the child's adaptation and coping with his/her chronic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the quality of life evaluated in patients with CKD is lower when compared to the general population or to control groups. 17 It is believed, considering the psychosocial aspects that make up the overall QOL of the individual, that the use of targeted psychosocial interventions have been shown to improve quality of life and lead to better treatment adherence.…”
Section: • Feelings Of the Adolescent Associated With The Disease Anmentioning
confidence: 99%